Performance of EGNSS-based Timing in Various Threat Conditions - Honkala, Salomon; Thombre, Sarang; Kirkko-Jaakkola, Martti; Zelle, Hein; Veerman, Henk; Wallin, Anders E.; Dierikx, Erik F.; Kaasalainen, Sanna; Söderholm, Stefan; Kuusniemi, Heidi (Institute of Electrical and Electronics Engineers (IEEE), 2019)
Today’s society is highly reliant on time and frequency synchronization, for example in communications systems and financial networks. Precise timing is more and more derived from satellite navigation receivers, which are unfortunately very susceptible to various signal threats. We studied the performance of Global Navigation Satellite System (GNSS) timing under different operating conditions, and tested the effectiveness of different techniques that improve timing receiver robustness. These features were tested under various threat scenarios related to specific vulnerabilities in GNSS-based timing, such as interference and navigation message errors, and their efficiency was analyzed against corresponding scenarios. We found that interference or meaconing-type spoofing can threaten GNSS timing, but can be detected by means of automatic gain control (AGC) and carrier-to-noise ratio based methods. GNSS interruptions due to interference can be bridged by a local oscillator holdover technique based on a Kalman filter whose parameters are based on a GNSS time solution. Navigation message errors are mitigated by the European Geostationary Navigation Overlay Service (EGNOS), and constellation-wide timing errors can be detected by the use of a dual-constellation (GPS-Galileo) cross-check. Dual-frequency operation for timing, in addition to mitigating first-order ionospheric effects, was found to be more robust to interference with the option to fall back to single frequency.
Keywords: global navigation satellite system; global positioning system; robustness; time dissemination; fi=Sähkötekniikka|en=Electrical Engineering|